Iowa Birdline update, April 1, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email for the Iowa Birdline update for April 1, 1991. Highlights include a Lesser Black-backed Gull, Bohemian Waxwing, Northern Goshawk, Le Conte's Sparrow, Long-tailed Duck and all three Swan species. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed